INKLUSI SOSIAL SEBAGAI TRANSFORMASI LAYANAN DI DINAS PERPUSTAKAAN DAN KEARSIPAN KABUPATEN ASAHAN - Sabriyanti, Aina; Batubara, Abdul Karim (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2023)
A library based on social inclusion is a library transformation that serves the information needs of all users without being limited to layers of social groups. So that the need for libraries as a place for literacy makes a transformation program to increase the role of the community to be better in participating in improving its social and economy. This research is a qualitative type with data collection techniques, namely interviews, observation and documentation at the Asahan District Library and Archives Service. The results of the study show that the transformation of social inclusion-based library services at the Asahan District Library and Archives Service provides changes or development of services that lead to provision or improvement of individual abilities to prepare themselves to improve their economy including: (1) knitting services for beginners, (2) learning computers, (3) library services, (4) story telling services, (5) mobile libraries and smart cars, and (6) socialization of reading and literacy services. This transformation program is carried out to make people, especially in Asahan Regency, able to have good skills in information, economy and digitalization.